2022
DOI: 10.1007/s00281-022-00971-3
|View full text |Cite
|
Sign up to set email alerts
|

The immunopathology of B lymphocytes during stroke-induced injury and repair

Abstract: B cells, also known as B lymphocytes or lymphoid lineage cells, are a historically understudied cell population with regard to brain-related injuries and diseases. However, an increasing number of publications have begun to elucidate the different phenotypes and roles B cells can undertake during central nervous system (CNS) pathology, including following ischemic and hemorrhagic stroke. B cell phenotype is intrinsically linked to function following stroke, as they may be beneficial or detrimental depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 100 publications
2
16
0
1
Order By: Relevance
“…These findings indicate that BCs are closely related to the pathogenesis of MMD. Prior research has also pointed towards the involvement of BCs during central nervous system pathology, including after ischemic and haemorrhagic strokes, further supporting their significance in MMD 50 . Additionally, a previous study using CIBERSORT reported increased levels of naive BCs in MMD patients, which aligns with our results 51 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate that BCs are closely related to the pathogenesis of MMD. Prior research has also pointed towards the involvement of BCs during central nervous system pathology, including after ischemic and haemorrhagic strokes, further supporting their significance in MMD 50 . Additionally, a previous study using CIBERSORT reported increased levels of naive BCs in MMD patients, which aligns with our results 51 .…”
Section: Discussionsupporting
confidence: 91%
“…B cells play a multifaceted role in the immune response to stroke, displaying both detrimental and restorative effects. After ischemic stroke, the compromised blood-brain barrier may permit B cells and other peripheral immune cells to enter ischemic brain tissue [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…B cells play a multifaceted role in the immune response to stroke, displaying both detrimental and restorative effects. After ischemic stroke, the compromised blood–brain barrier may permit B cells and other peripheral immune cells to enter ischemic brain tissue [25, 26]. These cells are crucial in modulating the progression of ischemic brain injury and influencing the secondary inflammatory response post‐stroke [15, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory response, coagulation abnormalities and poor nutritional status are pathophysiological mechanisms of AIS and also predictors of poor AIS prognosis [9][10][11] . Lymphocytes have a key regulatory function in post-AIS in ammation and have been shown to be predictors of exacerbating ischemic brain injury and deteriorating neurological function [12] . Platelet hyperactivity increases the risk of thromboembolism and atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 99%